JENIS – JENIS TEMA DALAM NOVEL ANAK RANTAU KARYA A. FUADI (KAJIAN ANALISIS ISI) - Meisya Natasha; Ade Rahima; Sujoko Sujoko (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this study is to discuss the types of themes in the novel Anak Rantau by A. Fuadi. This study aims to describe the types of themes in the novel by using Shipley's theory. This research is a qualitative descriptive. The data in this research are in the form of quotations relating to aspects of the types of themes in the Anak Rantau novel by A. Fuadi. In collecting the data, documentation technique is used. The result of this research is a description of the types of themes in the novel Anak Rantau by A. Fuadi (content analysis). The types of themes include physical themes, organic themes, social themes, egoistic themes, and divine themes, each of which has its own section.